2017
DOI: 10.2196/mhealth.6347
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity Tracker Testing in Youth (P.A.T.T.Y) Study: Content Analysis and Children’s Perceptions

Abstract: BackgroundActivity trackers are widely used by adults and several models are now marketed for children.ObjectiveThe aims of this study were to (1) perform a content analysis of behavioral change techniques (BCTs) used by three commercially available youth-oriented activity trackers and (2) obtain feedback describing children’s perception of these devices and the associated websites.MethodsA content analysis recorded the presence of 36 possible BCTs for the MovBand (MB), Sqord (SQ), and Zamzee (ZZ) activity tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Such features include social support and social comparison, which may motivate adolescents to be active, given that peer influence is associated with health behaviors such as physical activity [ 28 , 29 ]. However, little research has examined users’ awareness and use of the different features or functions of such devices or apps with youth [ 1 , 30 ]. Ascertaining how to change behavior through targeting specific aspects of the device and/or app, for example, would help to inform the development of future interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Such features include social support and social comparison, which may motivate adolescents to be active, given that peer influence is associated with health behaviors such as physical activity [ 28 , 29 ]. However, little research has examined users’ awareness and use of the different features or functions of such devices or apps with youth [ 1 , 30 ]. Ascertaining how to change behavior through targeting specific aspects of the device and/or app, for example, would help to inform the development of future interventions.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to use formative assessments to examine participant preferences for the Movband and dashboard in our planning and development of an SB intervention for girls and young women. Others studies have explored user preferences for Movband system in children [ 38 ] and college students [ 39 ] but not with the intent to develop an SB intervention. The study in children examined their perceptions of three commercially available activity-monitoring systems with the devices worn simultaneously and reported that the Movband system was the least “liked” among the participants [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others studies have explored user preferences for Movband system in children [ 38 ] and college students [ 39 ] but not with the intent to develop an SB intervention. The study in children examined their perceptions of three commercially available activity-monitoring systems with the devices worn simultaneously and reported that the Movband system was the least “liked” among the participants [ 38 ]. The possibility that the comparisons between the commercially available systems may have prejudiced the children’s opinions of the Movband system cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations